2015
DOI: 10.3109/00365521.2014.958094
|View full text |Cite
|
Sign up to set email alerts
|

Model for end-stage liver disease score as a predictor of short-term outcome in patients with drug-induced liver injury

Abstract: The outcome of patients with DILI was poor. MELD score and Hb were reliable predictors of short-term outcome in patients with DILI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…Our results also show that sex, age, latencies and DILI type are not correlated with DILI-associated mortality. This finding is consistent with studies from the USA (Chalasani et al 2015 ) and Korea (Jeong et al 2015 ). The data from the US study showed that the DILI-associated mortality was significantly higher in individuals with pre-existing liver disease (Chalasani et al 2015 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results also show that sex, age, latencies and DILI type are not correlated with DILI-associated mortality. This finding is consistent with studies from the USA (Chalasani et al 2015 ) and Korea (Jeong et al 2015 ). The data from the US study showed that the DILI-associated mortality was significantly higher in individuals with pre-existing liver disease (Chalasani et al 2015 ).…”
Section: Discussionsupporting
confidence: 93%
“…The MELD score is widely accepted as an accurate predictor of mortality across a broad spectrum of liver diseases (Said et al 2004 ; Martin et al 2014 ). The study from Korea also confirmed that the c-statistic for the MELD score alone was 0.93 and that the MELD score had strong discriminatory power and may be a reliable predictor of the prognosis in patients with DILI (Jeong et al 2015 ).…”
Section: Discussionmentioning
confidence: 71%
“…Since Model for End-Stage Liver Disease (MELD) score may predict mortality among DILI patients, 15 we examined the accuracy of different MELD score cut-offs for incident ALF. Among KPNC patients who had INR measured at DILI diagnosis, MELD score was calculated by: 3.78*ln[total bilirubin (mg/dL)] + 11.2*ln[INR] + 9.57*ln[creatinine (mg/dL)] + 6.43.…”
Section: Methodsmentioning
confidence: 99%
“…Cholestatic DILI usually will generally resolve within 3–12 months after the withdrawal of hepatoxic drugs [80], but a few of those patients may have prolonged course and finally develop into severe vanishing bile duct syndrome and cholestatic cirrhosis, which indicates a poor prognosis. A retrospective study of South Korea [142] suggested that the percentage of 30-day poor prognosis after admission was up to 13.1% among 213 patients with DILI. In addition, the Model for End-Stage Liver Disease (MELD) score and the level of hemoglobin were found to be independent predictors for short-term prognosis of those patients, while the clinical patterns of liver injury (hepatocellular injury, mixed or cholestatic pattern) upon admission were less correlated with the short-term prognosis at 30 days.…”
Section: Prognosis Of Dilimentioning
confidence: 99%